Human CD4(+) T Helper Cell Responses after Tick-Borne Encephalitis Vaccination and Infection - Aberle, Judith H. (PLoS One, 2015)
Tick-borne encephalitis virus (TBEV) is a human-pathogenic flavivirus that is endemic in large parts of Europe and Asia and causes severe neuroinvasive illness. A formalin-inactivated vaccine induces strong neutralizing antibody responses and confers protection from TBE disease. CD4(+) T cell responses are essential for neutralizing antibody production, but data on the functionalities of TBEV-specific CD4(+) T cells in response to vaccination or infection are lacking. This study provides a comprehensive analysis of the cytokine patterns of CD4(+) T cell responses in 20 humans after TBE vaccination in comparison to those in 18 patients with TBEV infection. Specifically, Th1-specific cytokines (IFN-γ, IL-2, TNF-α), CD40 ligand and the Th1 lineage-specifying transcription factor Tbet were determined upon stimulation with peptides covering the TBEV structural proteins contained in the vaccine (C-capsid, prM/M-membrane and E-envelope). We show that TBEV-specific CD4(+) T cell responses are polyfunctional, but the cytokine patterns after vaccination differed from those after infection. TBE vaccine responses were characterized by lower IFN-γ responses and high proportions of TNF-α(+)IL-2(+) cells. In vaccine-induced responses—consistent with the reduced IFN-γ expression patterns—less than 50% of TBEV peptides were detected by IFN-γ(+) cells as compared to 96% detected by IL-2(+) cells, indicating that the single use of IFN-γ as a read-out strongly underestimates the magnitude and breadth of such responses. The results provide important insights into the functionalities of CD4(+) T cells that coordinate vaccine responses and have direct implications for future studies that address epitope specificity and breadth of these responses.